Clinical importance of borderline proteinuria in nonazotemic cats and evaluation of other risk factors for the development of chronic kidney disease - Femke Mortier; Sylvie Daminet; Sofie Marynissen; Joren Verbeke; Dominique Paepe (Journal of Veterinary Internal Medicine)
Abstract Background Borderline proteinuria is associated with decreased survival in cats with azotemic chronic kidney disease (CKD). Objectives Determine the clinical importance of borderline proteinuria in nonazotemic cats. Animals A total of 201 healthy client‐owned cats ≥7 years of age; 150 nonproteinuric (urinary protein : creatinine ratio [UPC] <0.2) and 51 borderline proteinuric (UPC 0.2‐0.4). Methods Prospective study. Cats were thoroughly screened and subsequently examined every 6 months for 2 years. Kaplan‐Meier curves were compared between nonproteinuric and borderline proteinuric cats. Univariable and multivariable Cox models were fit to determine the relationship between development of renal disease and potential risk factors such as age, sex, breed, weight, dental disease, blood pressure, serum creatinine concentration (sCrea), serum symmetric dimethylarginine concentration (sSDMA), blood urea nitrogen concentration, urine specific gravity (USG), and UPC. Results Significantly more cats with borderline proteinuria at inclusion developed renal disease (International Renal Interest Society [IRIS] ≥ stage 2 CKD or renal proteinuria; log‐rank P = .004) or died (log‐rank P = .02) within 2 years, compared with nonproteinuric cats. In the multivariate analysis, IRIS stage 1 CKD (persistent USG <1.035 or sSDMA >14 μg/dL; hazard ratio [HR], 4.2; 95% confidence interval [CI], 2.0‐8.8; P < .001), sCrea ≥1.6 mg/dL (≥140 μmol/L; HR, 2.6; 95% CI, 1.1‐6.4; P = .04), borderline proteinuria (HR, 2.5; 95% CI, 1.2‐5.2; P = .01), and age at inclusion (HR, 1.3; 95% CI, 1.2‐1.5; P < .001) were significantly associated with diagnosis of renal disease 6 months later. Conclusions and Clinical Importance Borderline proteinuria should receive more attention in healthy mature adult and senior cats because it is associated with renal disease and death.